Peran Halal Tourism dalam Meningkatkan Daya Saing Ekonomi Islam di Sektor Pariwisata - Ahmad Martin Cahyadi; Rahma Raya Fitriana; Raisya Oktaviana; Rania Purnama Aulia; Wahidatul Athiya; Edi Suresman (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study examines the role of halal tourism in enhancing destination competitiveness and strengthening the Islamic economy within the tourism sector. This research employs a systematic literature review to synthesize findings from relevant academic sources. The results indicate that halal tourism contributes significantly to destination competitiveness by increasing tourist arrivals and encouraging product diversification. In addition, it supports the development of micro, small, and medium enterprises (MSMEs) and promotes local economic growth through a multiplier effect. Halal tourism also fosters ethical business practices and sustainable tourism development aligned with Islamic principles. However, its implementation faces key challenges, including limited infrastructure, complex halal certification procedures, and perceptions of exclusivity among non-Muslim tourists. Therefore, strategic efforts are required to improve Muslim-friendly infrastructure, streamline certification processes, strengthen MSME capacity through training and digitalization, and adopt inclusive branding strategies. These measures are expected to enhance the competitiveness, resilience, and sustainability of halal tourism destinations in the global market.